Pengaruh Volume Perdagangan dan Return terhadap Bid-Ask Spread dengan Model Koreksi Kesalahan - Barbara Gunawan (Universitas Muhammadiyah Yogyakarta, Indonesia, 2005)
This study aimed to examine the effect of trading volume and return to the bid-ask spread pharmaceutical industry shares listed on the JSE during 2003. This study uses regression analysis techniques. The results showed that the only variable return that proved false. However, for variable trading volume proved the absence of forgery.